ANALISIS KINERJA KEUANGAN PENGELOLAAN ALOKASI DANA KELURAHAN BERDASARKAN RASIO EFEKTIVITAS PADA TAHUN 2019-2021 (STUDI KASUS PADA KANTOR KELURAHAN PETAMANAN KOTA PASURUAN) - Alfiah Alfiah; Dwi Dayanti Oktavia; Tifanny Septia Wibowo (JAKA - Jurnal Jurusan Akuntasi, 2023)
This research was conducted to test how well the financial performance of the Village Fund allocation management is based on the effectiveness ratio at the Petamanan Village Office, Pasuruan City. The population in this study is the financial report of Village Fund allocation from the Petamanan Village Office, Pasuruan City. The sample data that is processed is the financial report on Village Fund allocations in 2019-2021, by going through the purposive sample stage. Data collection techniques used in this study were interviews, documents, and literature studies. The data analysis technique that will be used is descriptive qualitative using the effectiveness ratio formula. The results of the study showed that the financial performance of the Village Fund allocation at the Pasuruan Municipality's Petamanan Office for 2019-2021 has generally been well managed. This is indicated by the results of the calculation of the effectiveness ratio of the financial statements of the Village Fund allocation which are categorized as effective, which is the average value of the effectiveness ratio 99% These results indicate that the ability of the Petamanan Village government of Pasuruan City to achieve the Village Fund target has been running Good.